The germline gene encoding DNA polymerase alpha in the hypotrichous ciliate Oxytricha nova is extremely scrambled. - Hoffman, D C (1996)
We report the structure of the micronuclear (germline) gene encoding the large catalytic subunit of DNA polymerase alpha (DNA pol alpha) in the ciliate Oxytricha nova. It contains 44 internal eliminated segments (IESs) that divide the gene into 45 macronuclear-destined segments (MDSs) that are in a non-randomly scrambled order with an inversion near the gene center. Odd numbered MDSs 29-43, containing 230 bp out of a total of 4938 bp of macronuclear sequence, are missing from the 14 kb cloned gene. The missing MDSs have not been located but are at least several kilobases from the main body of the gene. The remarkably scrambled DNA pol alpha gene must be extensively cut, re-ordered and spliced and an inversion must occur to produce an unscrambled, functional version of the gene during development of a new macronucleus. Unscrambling is hypothesized to occur by a homologous recombination mechanism guided by repeat sequences at MDS ends.